Karakterisasi Material Braket Kawat Gigi Dalam Larutan Saliva Buatan - Nurbaiti Nurbaiti; Hendri Van Hoten; Putra Bismantolo (METAL: Jurnal Sistem Mekanik dan Termal, 2021)
This research is about Characterization of Metal and Ceramic Brace Brackets in Artificial Saliva Solution. The shape of teeth in humans is different, some are neat and some are not. With the times, the problem of untidy teeth can be fixed using braces / braces. Nowadays, the use of braces / braces is not only for straightening teeth but for lifestyle and to support a more attractive and attractive appearance. Braces consist of brackets and curved wires. Braces brackets can be made from a variety of materials, for example: metals, ceramics and composites. This study was directed to determine the biocompatible properties of the bracket in the body by looking at the elemental content after immersion with a solution of saliva (artificial saliva) for approximately 4 weeks. The results of the hardness examination showed an increase between before and after immersion. The chemical composition examination using XRD (X-Ray Diffraction) has not shown any significant changes between the materials before and after immersion. XRD results show that there are no corrosive materials or other hazardous materials on the surface of the braces bracket material.